Persepsi Guru terhadap Penerapan Konsep Merdeka Belajar di Sekolah Dasar - Faisal, Rifki; Rahman, Syarifah Aeni; Babo, Rosleny (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2023)
This study aims to determine the teacher's perception of the application of the concept of independent learning at SD Negeri Alluka. The type of research used is descriptive qualitative with a phenomenological approach. Data collection was carried out using questionnaires or interviews. Based on the results of the research through the interview process with several question points, the result was that the teacher's perception of the application of independent learning was good, but what was still an obstacle in implementing independent learning was the lack of understanding of teachers regarding independent learning broadly. Based on the results of the study, it can be concluded that the teacher's perception of the application of independent learning at SD Negeri Alluka is good, but there is still a need for special socialization to provide a broad understanding of independent learning.